KENAIKAN DAN PENYEDERHANAAN TARIF CUKAI UNTUK MENURUNKAN PENGELUARAN KONSUMSI ROKOK DAN PREVALENSI PEROKOK REMAJA - Muhammad Maulana Makarim; Aditya Subur Purwana (JURNAL INFORMASI, PERPAJAKAN, AKUNTANSI, DAN KEUANGAN PUBLIK, 2022)
The prevalence of smokers in Indonesia is one of the highest in the world and is expected to continue to increase. This cannot be separated from the high household expenditures for consuming cigarettes and smoking habits that began in the times of youth. In order to decrease cigarette consumption and smoking habits among adolescents, the government is trying to control the rate by increasing tariffs and simplifying the structure of the tobacco excise tariffs. However, as seen from the data, the expenditures for household consumption in Indonesia for cigarette commodities has been increasing from year to year. Meanwhile, the prevalence of youth smoking did not show a significant decrease. Based on this, the authors conducted a study that aims to determine the effect of increasing tariffs and simplifying the structure of tobacco excise rates on household cigarette consumption expenditure and the prevalence of youth smokers. This study uses random effect model to analyse the panel data for 34 provinces in Indonesia in the period 2015 until 2019. The results reveals that an increase in tariffs and simplification of the tariff structure has a significant and negative effect on household cigarette consumption expenditure, and have a significant and positive effect on the prevalence of adolescent smoking.